2022
DOI: 10.3389/fphar.2022.916732
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin Ameliorates Renal Dysfunction, Oxidative Stress, Inflammation, and Apoptosis and Upregulates Nrf2/HO-1 Signaling in a Rat Model of Gentamicin-Induced Nephrotoxicity

Abstract: Gentamicin (GEN) is a bactericidal aminoglycoside known to cause nephrotoxicity. Formononetin (FN) is a potent flavonoid that exhibits numerous promising pharmacological activities. In this study, we have assessed the nephroprotective efficacy of FN against GEN-induced renal injury in rats. Rats were orally administered with FN (60 mg/kg/day, for 2 weeks) and were co-treated with intraperitoneal (i.p.) injection of GEN (100 mg/kg/day) during the days 8–14. GEN-treated rats demonstrated increased urea and creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
(111 reference statements)
5
9
0
Order By: Relevance
“…Our results revealed significant (p < 0.001) downregulation in testicular Nrf2/HO-1 gene expression in the gentamicin group in relation to control rats. This result coincides with Althunibat et al [64], who reported that gentamicin administration downregulated immunoexpression of Nrf2 and HO-1 in a rat model of gentamicin-induced nephrotoxicity. Nrf2 is considered a redox-sensitive transcription factor that is sequestered by Keap-1 in the cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed significant (p < 0.001) downregulation in testicular Nrf2/HO-1 gene expression in the gentamicin group in relation to control rats. This result coincides with Althunibat et al [64], who reported that gentamicin administration downregulated immunoexpression of Nrf2 and HO-1 in a rat model of gentamicin-induced nephrotoxicity. Nrf2 is considered a redox-sensitive transcription factor that is sequestered by Keap-1 in the cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…Since these enzymes are found in the cytosol and released into the blood after liver damage, this spike is attributed to damaged liver cells. This outcomes was in agreement with the results reported by [38][39]. The elevation in Liver enzyme since they are located in the cytoplasm and released into the bloodstream following cellular damages signaling the development of hepatotoxicity, level has been linked to the damage to the structural integrity of the liver…”
Section: Effect Of Mtx and Montelukast On Liver Function Test Effect ...supporting
confidence: 92%
“…Although activated by ROS under physiological conditions, Nrf2 downregulation has been reported under conditions of excessive and prolonged ROS [ 31 , 58 , 59 , 60 ]. Extensive evidence indicates that various naturally occurring compound-mediated Nrf2 activation can protect against drugs/chemicals-induced renal injury [ 58 , 59 , 61 ]. Several investigations have reported the role of Nrf2 in mediating the protective role of TA [ 20 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Nrf2 modulates the response to OS by regulating the expression of numerous genes, including ferritin and HO-1, supported by the antioxidant responses [ 63 ]. Accordingly, a previous study showed that TA prevented skin cancer by inducing Nrf2 expression and downstream target genes in JB6 P+ cells via the CpG demethylation process [ 61 ]. Furthermore, Xie et al [ 62 ] reported that TA could protect human RPE cells against OS-induced apoptosis via activating the expression of Nrf2 by facilitating its translocation to the nucleus.…”
Section: Discussionmentioning
confidence: 99%